Relative recoilless F-factors in REFeO3 (RE = rare-earth La, Pr, Nd and Sm) orthoferrites synthesized by self-combustion method (2016)
ABSTRACT: In this work, rare-earth orthoferrites polycrystalline compounds REFeO3 (REFO) with RE = rare-earth La, Pr, Nd and Sm were synthesized by the self-combustion method. A direct correlation between the magnitude of the magnetic hyperfine field and the FeAO1AFe bond angles was observed. From transmission Mössbauer spectra recorded at room-temperature, relative recoilless F-factors for these REFO compounds were estimated. The method applied to perform this calculation was based on the determination of two subspectral areas present in a mixture of known amounts of the compound under study and a standard sample (a-Fe). For that purpose spectra were thickness-corrected and fitted using lorentzian lines. The so obtained factors were F-REFeO3 (RE = rare-earth La, Pr, Nd and Sm): 1.30 ± 0.02, 1.08 ± 0.04, 1.15 ± 0.05, 1.18 ± 0.08 respectively. The absolute recoilless factors obtained by this method had an average relative error around 11% in comparison with the values predicted by the Debye model.